2010
DOI: 10.1038/cddis.2010.37
|View full text |Cite
|
Sign up to set email alerts
|

MEK–ERK-dependent multiple caspase activation by mitochondrial proapoptotic Bcl-2 family proteins is essential for heavy ion irradiation-induced glioma cell death

Abstract: Recently developed heavy ion irradiation therapy using a carbon beam (CB) against systemic malignancy has numerous advantages. However, the clinical results of CB therapy against glioblastoma still have room for improvement. Therefore, we tried to clarify the molecular mechanism of CB-induced glioma cell death. T98G and U251 human glioblastoma cell lines were irradiated by CB, and caspase-dependent apoptosis was induced in both cell lines in a dose-dependent manner. Knockdown of Bax (BCL-2-associated X protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 39 publications
(68 reference statements)
1
36
0
Order By: Relevance
“…Several data obtained with regard to U251 cell line was found to be in line with those described by Tomiyama ' s group (Tomiyama et al 2010). However, we can report on the signifi cance of Erk1/2 activation in photon irradiation-induced glioblastoma cell death as well.…”
Section: Cancer Cell Radiosensitization By Parp Inhibitor 1157supporting
confidence: 79%
See 1 more Smart Citation
“…Several data obtained with regard to U251 cell line was found to be in line with those described by Tomiyama ' s group (Tomiyama et al 2010). However, we can report on the signifi cance of Erk1/2 activation in photon irradiation-induced glioblastoma cell death as well.…”
Section: Cancer Cell Radiosensitization By Parp Inhibitor 1157supporting
confidence: 79%
“…We are also aware of signal transduction element coding gene mutations having impact on anticancer therapy (McCubrey et al 2011). Besides, the Ras-Raf-MEK-Erk1/2 cascade, which is predominantly known as a promoter of cell viability, diff erentiation, survival and tumour progression, can play an undisputable role in cell death and inhibition of proliferation in U251 cell line (Arai et al 2004, Hagan et al 2007, Lu et al 2010, Tomiyama et al 2010. Th is fact is of outstanding signifi cance in cases like k-Ras Figure 7.…”
Section: Discussionmentioning
confidence: 95%
“…These results indicate that the Ezh2 gene plays a key role in maintaining the growth and invasion of neuroblastoma. Studies have also shown that the apoptosis of glioma cells is closely related to the mitochondrial pathway (14,15). In this study, we showed that the silencing of the Ezh2 gene leads to changes in the levels of Bax and Bcl-2.…”
Section: Introductionmentioning
confidence: 60%
“…The current study showed that cell differentiation is a complex process with multiple stages, and may be related to multiple intracellular signal pathways, such as the ERK, PI3, K2A, KT, and Wnt signal pathways (Tomiyama et al, 2010). Of these pathways, the ERK signal pathway has the closest relationship with the proliferation and differentiation of tumor cells, and its activation is negatively correlated with tumor cell proliferation.…”
Section: Discussionmentioning
confidence: 96%